2021
DOI: 10.1002/crat.202100014
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Growth of Silver Dendrites Regulated by Preferential Adsorption of Nitrate Ions on Crystal Facets

Abstract: Dendritic structures are widely present in nature, from snowflakes to dendritic cells. However, their formation mechanisms are unclear, which causes long unsolved engineering problems, such as lithium dendrites. Here a strategy to control the growth of dendritic structures by the selective adsorption of ions on crystal facets is reported. Silver particles are synthesized by galvanic replacement reaction and the growth anisotropy of crystals is regulated by changing the concentration of nitrate ions in silver n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Huang et al. have also reported the controlled growth of AgNDs by preferential adsorption of nitrate ions during GD reaction . In the GD reaction, frequently used templates are surfactants, metal, or nonmetals with specific structures such as Si, nickel, zinc, iron, and anodic aluminum oxide (AAO). Recently, in 2021, Athavale et al reported comprehensive details in the fabrication of metal NDs on various templates and their applications in SERS sensing .…”
Section: Metal Nanodendrites Decorated On Si Substratementioning
confidence: 99%
“…Huang et al. have also reported the controlled growth of AgNDs by preferential adsorption of nitrate ions during GD reaction . In the GD reaction, frequently used templates are surfactants, metal, or nonmetals with specific structures such as Si, nickel, zinc, iron, and anodic aluminum oxide (AAO). Recently, in 2021, Athavale et al reported comprehensive details in the fabrication of metal NDs on various templates and their applications in SERS sensing .…”
Section: Metal Nanodendrites Decorated On Si Substratementioning
confidence: 99%